Analyse socioéconomique de la transformation traditionnelle du manioc à Kindu et ses environs dans la province Maniema en République Démocratique du Congo - Martin MUTUZA BAKUZEZIA; Bernard SHABANI KASONGO; Blaise BILEMBO MALONGA; Ernest WATANGA LUKANGE; Théophile KIBISA WA KIBISA (IJRDO - Journal of Social Science and Humanities Research, 2019)
A cassava study was conducted in Kindu and surrounding areas in the Maniema Province of the Democratic Republic of Congo. The objective of this study is to carry out a socioeconomic analysis on cassava fresh root supply, the varieties and equipment used, the actors involved, the transformation system and the related constraints. The survey was conducted from February 20 to June 20, 2019 on a random sample of 150 households. The data were processed and analyzed using Excel 2010 software. The results obtained showed that 84% of the respondents are women, 95% are between the ages of 18 and 60, 78.2% of whom were women. in primary school and 0.9% illiterate. The cassava cultivars used in processing are all bitter and come mostly from family farms (94%). The equipment used for this transformation is artisanal in all households, family size with manual operation and dealing with limited quantities of lower quality products. However, for 20 kg of fresh cassava roots purchased at 1500 FC, the gross margin is 2300 FC for the Lomata (profitability of 92%) and 1700 FC for the chikwangues (profitability of 63%). However, further studies are needed to analyze the profitability of production and marketing of cassava processing products by both traditional and improved methods.